Upgrading options for organic cashew producers of El Salvador in the global chain - Guzmán, Karla Melissa (2015)
The article analyzes the global organic cashew chain in El Salvador. The relevance is to analyze activities that generating incomes and are compatible with the exploitation of resources and ensure the competitive improvement of the actors in the different links of a chain. The Global Commodities Chain approach is used in the study, where the concept of upgrading acquires special relevance to attempt higher incomes in the global chain. Upgrading indicators shows potential improvements in some areas: Management of technical, coordination, diversification and product differentiation. The results showing the conditions of the institutional environment, complexity and governance in the chain as well as foreign competitors innovations are the factors that determine the improvement.